2017
DOI: 10.1002/art.40045
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐Array Analysis in Sporadic Inclusion Body Myositis Reveals HLA–DRB1 Amino Acid Heterogeneity Across the Myositis Spectrum

Abstract: ObjectiveInclusion body myositis (IBM) is characterized by a combination of inflammatory and degenerative changes affecting muscle. While the primary cause of IBM is unknown, genetic factors may influence disease susceptibility. To determine genetic factors contributing to the etiology of IBM, we conducted the largest genetic association study of the disease to date, investigating immune‐related genes using the Immunochip.MethodsA total of 252 Caucasian patients with IBM were recruited from 11 countries throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Contrary to previous results that HLA-DRB4 is protective and ameliorates the risk effect of HLA-DRB1*03:01 [17], no HLA alleles were found to modify disease onset or severity of IBM in this study. Furthermore, in agreement with a study performed in an Australian cohort, there was no distinct HLA association with anti-cytosolic 5’-nucleotidase 1A (anti-cN1A) positivity [19,23]. …”
Section: Immune Systemsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to previous results that HLA-DRB4 is protective and ameliorates the risk effect of HLA-DRB1*03:01 [17], no HLA alleles were found to modify disease onset or severity of IBM in this study. Furthermore, in agreement with a study performed in an Australian cohort, there was no distinct HLA association with anti-cytosolic 5’-nucleotidase 1A (anti-cN1A) positivity [19,23]. …”
Section: Immune Systemsupporting
confidence: 90%
“…Nonetheless, since first described by Garlepp et al in 1994, the Human Leukocyte Antigen (HLA) locus has been shown repeatedly to contain the strongest risk alleles for the development of IBM (Table 1) [1619]. Recently, the Myositis Genetics Consortium (MYOGEN) analyzed immune-related genes in 252 Caucasian IBM patients and 1,008 ethnically-matched controls from 11 countries using the Illumina Immunochip array [19]. Variants within the HLA locus were the only single-nucleotide polymorphisms (SNPs) to reach genome-wide significance (p < 5 × 10 −8 ).…”
Section: Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that several autoimmune diseases, including the IIMs, share genetic overlap for susceptibility to disease [ 14 , 15 ]. In line with this evidence, a recent study hypothesized that there may be shared immune loci associated with IBM [ 16 ▪▪ ].…”
Section: Immune-related Genes In Inclusion Body Myositismentioning
confidence: 88%
“…8 Written informed consent was obtained from all patients with approval from research ethics committees of institutional review boards at each participating centre. Patients were enrolled in to MYOGEN if they fulfilled Bohan and Peter criteria for PM and adult and juvenile DM,8 or Griggs, Medical Research Council (MRC) or European Neuromuscular Centre (ENMC) criteria for patients with IBM 14. Shared control genotypes were drawn from a pool of 15 651 individuals from 12 countries as described previously 8.…”
Section: Methodsmentioning
confidence: 99%